2021
DOI: 10.17957/ijab/15.1727
|View full text |Cite
|
Sign up to set email alerts
|

Bioassays Guided Fractionation of Ageratum conyzoides Extract for the Identification of Natural Antifungal Compounds against Macrophomina phaseolina

Abstract: Macrophomina phaseolina (Tassi) Goid. is a soil-borne fungal pathogen causing diseases in more than 500 plant species. The present study aimed to identify possible antifungal constituents in different parts of billygoat-weed (Ageratum conyzoides L.) through bioassays guided fractionation for the control of M. phaseolina. Extracts of different parts of the weed were made in methanol and antifungal bioassays were conducted using 1, 2, 3, 4 and 5% concentrations of the extract. Stem extract caused the highest inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…All fractions exhibited a reduction in pathogen biomass over the control. Several compounds from ACE [such as 2H-1-benzopyran, 7-dimethoxy-2,2-dimethyl, hexadecanoic acid, 11-octadecenoic acid, methyl ester, 1,2-benzenedicarboxylic acid, and mono(2-ethylhexyl) ester] could exert biopesticide potential [ 65 ]. However, these isolated compounds should be further evaluated separately for their potential application in agriculture as a biopesticide.…”
Section: Effectiveness Of Secondary Metabolites From a Conyzoidesmentioning
confidence: 99%
“…All fractions exhibited a reduction in pathogen biomass over the control. Several compounds from ACE [such as 2H-1-benzopyran, 7-dimethoxy-2,2-dimethyl, hexadecanoic acid, 11-octadecenoic acid, methyl ester, 1,2-benzenedicarboxylic acid, and mono(2-ethylhexyl) ester] could exert biopesticide potential [ 65 ]. However, these isolated compounds should be further evaluated separately for their potential application in agriculture as a biopesticide.…”
Section: Effectiveness Of Secondary Metabolites From a Conyzoidesmentioning
confidence: 99%
“…Both qualitative and quantitative analyses can be performed with the help of HPLC and mass spectrometry. Moreover, recent studies revealed that GC-MS is a good technique for the identification of compounds present in different plant parts Javaid, 2019, 2020a, b;Banaras et al, 2020Banaras et al, , 2021. The presence of phytochemicals in C. fistula is admitted and discovered as well but still there may be many compounds which are yet to be discovered.…”
Section: Introductionmentioning
confidence: 99%
“…The plants possess phytochemical compounds, which are effective against different pests including insects, fungi, virus, nematode, bacteria etc. (Khan et al 2020;Javaid et al 2020Javaid et al , 2021. Thus, plant based materials can be used as a substitute for synthetic pesticides in order to ensure the safety of human and the environment (Engindeniz and Engindeniz 2013; Khan and Javaid 2020; Banaras et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…(Khan et al 2020;Javaid et al 2020Javaid et al , 2021. Thus, plant based materials can be used as a substitute for synthetic pesticides in order to ensure the safety of human and the environment (Engindeniz and Engindeniz 2013; Khan and Javaid 2020; Banaras et al 2021).…”
Section: Introductionmentioning
confidence: 99%